Pengaruh Terapi Reminiscence Terhadap Harga Diri Lansia dengan Penyakit Kronik di Kelurahan Bubulak Tahun 2012 - Utami, Tantri Widyarti; Ariani, Ni Putu (Jurnal Keperawatan Jiwa, 2014)
Old age is the final stage of the human life cycle. At this stage, individuals experience a setback various functions and capabilities, resulting in older adults experiencing chronic disease that affects the elderly dignity. The purpose of this research is to gain influence reminiscence therapy for the dignity of elderly with chronic diseases in Bubulak Village Bogor in 2012. The benefit of this research is as a guide for the nurses in conducting reminiscence therapy in the elderly with chronic diseases and as an evidence based. The hypothesis of this study is that âreminiscence therapy can increase self-esteem of elderly with chronic diseasesâ. The design used was "Quasi experimental with pre and post test with control group" and with reminiscence therapy intervention. The sampling is done as purposive sampling with a sample of 108 elderly, consisted of 54 intervention groupand 54 control group. Elderly esteem was measured using Rosenberg self-esteem scale instrument and analyzed by univariate and bivariate analyzes. Results of this study demonstrate dignity of elderly with chronic diseases who received reminiscence group therapy significantly increased with p-value of 0.000, whereas no change in the control group (p-value of 0.322). Reminiscence recommended the dignity of elderly with chronic diseases. This research is expected to enhance the ability of nurses in psychosocial therapy in elderly.